Assessment of Climate Change by Dendrochronological Methods in Polissya - Koval, Iryna; Meshkova, Valentyna; Maksymenko, Nadiya; Roibu, Catalin-Constantin; Obolonik, Iryna (SHS web of conferences, 2021)
Dendrochronological methods were used to study the response of Quercus robur L. to climate change in Polissya. Negative pointer years (1950, 1976, 1995, 1999, 2002, 2008, and 2011) resulted from the precipitation deficiency during the growing season, cold or extremely warm winters, and abnormal early-spring temperatures. Positive pointer years (1967, 1997, 2001, and 2007) had a favorable heat and moisture balance. Dendroclimatic analysis of oak regional tree-ring chronology showed that during the spring and summer terms of 1980 - 2013, as compared to the previous 1946–1979, there a decrease in the positive influence of temperatures on the oak radial growth. In the second period, the negative impact of precipitation during the cold period on radial growth increased. The adverse impact of April precipitation on radial growth for both periods was revealed as well as the positive influence of July precipitation in the first period and precipitation in June and July in the second one. The increased influence of temperatures and precipitation on the oak radial growth in 1980 - 2013, as compared to previous 1946-1979, indicates an increase in the tree sensitivity to climate change in the second period.